EFEKTIVITAS KEPEMIMPINAN GURU TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK - admin, admin; Sumarni, Ai Laila; Amin, M. Sukron (Prodi PAI IAILM Suryalaya, 2021)
This study aims to find out and analyze the influence of teacher leadership on the character building of students in MIN 12 Ciamis. This research is expected to be useful in developing science, improvement and reference for researchers, teachers, and principals in carrying out education in the future. The method used for this research is descriptive quantitative method. Population of 370 people and sample as many as 25 respondents with Purposive Sampling technique. Data collection techniques using questionnaires, interviews, observations and documentation along with guidelines. Data processing is done through descriptive data processing with Rank Spearman correlation (r_s). Based on the results of data processing obtained that the influence of teacher leadership on the character building of students in MIN 12 Ciamis has a positive and significant influence with a very high category, with r_s = 0.82 at intervals of 0.81 – 1.00. The calculation result of thitung and ttabel is 6.8634 ≥ 1.714 then Ha is accepted and H0 is rejected. Teacher leadership influenced the character building of learners by 67.24%, and the remaining 32.76% was determined by other factors such as from inside and outside the learners.